2020
DOI: 10.1088/1742-6596/1465/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

HOTS student worksheet to identification of scientific creativity skill, critical thinking skill and creative thinking skill in physics learning

Abstract: In the learning context of 21st century, teachers encounter many challenges in optimizing the process and the outcome of learning. Students who have higher order thinking skills will be able to think of scientific creativity, critical thinking and creative thinking. In this study, identification is done by measuring the ability of scientific creativity, critical thinking and creative thinking skills by HOTS student worksheet. The result showed that student’s scientific creativity with 6 indicators need to be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
1
15
0
3
Order By: Relevance
“…Answers are emphasized on the quantity, usefulness, and diversity of answers, which can be measured by several indicators, including fluency, flexibility, originality, and elaboration. Creative thinking skills are part of higher-order thinking skills that enter the cognitive domain which includes analyzing, evaluating, creating [48]. High order thinking skills (HOTS) are classified in the cognitive domain of questions C-4, C-5 and C-6.…”
Section: Creative Thinking Abilitymentioning
confidence: 99%
“…Answers are emphasized on the quantity, usefulness, and diversity of answers, which can be measured by several indicators, including fluency, flexibility, originality, and elaboration. Creative thinking skills are part of higher-order thinking skills that enter the cognitive domain which includes analyzing, evaluating, creating [48]. High order thinking skills (HOTS) are classified in the cognitive domain of questions C-4, C-5 and C-6.…”
Section: Creative Thinking Abilitymentioning
confidence: 99%
“…It boosts students' cognitive aspect as well as their awareness to assess and evaluate information critically (Changwong, Sukkamart, & Sisan, 2018). Furthermore, it is considered as High Order Thinking (HOT) skills, which consist of some components such as fluency, flexibility, and originality (Astutik, Mahardika, Indrawati, Sudarti, & Supeno, 2020;Sriwongchai, 2015;Yusof & Seman, 2018). In general, fluency refers to the ease in generating several concepts in the creative process; flexibility relates to the capacity to abandon the old way of thinking and embrace new concepts or a new path, and originality involves to produce unpredictable, unusual or unique ideas (Handayani, Hajidin, Duskri, & Maidiyah, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As developed by Wahyuni et al (2020), worksheets are developed to facilitate authentic problem-solving skills of students in the learning process. The goal of students' worksheet-based higher-order thinking skills is to explore students' high-level thinking skills, and each question is prepared by paying attention to indicators and aspects of scientific creativity skills, critical thinking, and creative thinking (Astutik et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the description, the question of this study is whether students are able to solve problems in biological materials provided using creative problem-solvingbased worksheets in high school? Astutik et al (2020) suggested that more research is needed on workseets based on higher-order thinking skills at the primary, secondary, and upper education levels. Asma et al (2020) also suggested designing worksheets to be more interactive and accommodate every element in the scientific process…”
Section: Introductionmentioning
confidence: 99%